2020
DOI: 10.1002/smll.202002733
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Multi‐Stimuli Nanocomposite Therapeutic: Docetaxel Targeted Delivery and Synergies in Treatment of Human Breast Cancer Tumor

Abstract: To further improve the efficiencies of the established drugs, various treatment strategies, such as preparation of protein-drug conjugates and the design of nanoscale drug-carriers, are used to increase the efficacy of therapeutic agents. [6-8] Several effective nanocarrier systems were designed to deliver anti-cancer cytotoxic agents to tumor cells with high selectivity and efficacy while minimizing negative side effects. [9,10] Drug nano-carriers provide multiple advantages, such as convenient uptake and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 88 publications
1
72
0
Order By: Relevance
“…Overall, the tumor inhibition was achieved by a combination of magnetically targeted delivery by iron NPs, pH and temperature-selective docetaxel release by PVA component, photothermal effect of gold NPs, and anti-tumor effects of docetaxel. This study reflects the successful report of iron–gold nanohybrids as a single system for multifunctional uses in cancer therapy [ 105 ]. In another example, Yun Quan-Li et al have covalently attached a cytotoxic agent such as methotrexate to iron–gold alloy NPs and reported that with the increase in the applied magnetic field, the release of methotrexate increased in an incremental manner [ 111 ].…”
Section: Iron–gold Bifunctional Nanoparticlessupporting
confidence: 78%
See 1 more Smart Citation
“…Overall, the tumor inhibition was achieved by a combination of magnetically targeted delivery by iron NPs, pH and temperature-selective docetaxel release by PVA component, photothermal effect of gold NPs, and anti-tumor effects of docetaxel. This study reflects the successful report of iron–gold nanohybrids as a single system for multifunctional uses in cancer therapy [ 105 ]. In another example, Yun Quan-Li et al have covalently attached a cytotoxic agent such as methotrexate to iron–gold alloy NPs and reported that with the increase in the applied magnetic field, the release of methotrexate increased in an incremental manner [ 111 ].…”
Section: Iron–gold Bifunctional Nanoparticlessupporting
confidence: 78%
“…Nanohybrids combining magnetic and gold nanoparticles facilitate the selective release of drugs [ 105 ] which are successfully employed for gene [ 106 ] and drug delivery applications [ 23 , 107 , 108 , 109 , 110 ]. For instance, Reza et al has reported a nanohybrid of iron oxide and gold NPs with a polymer such as PVA and cytotoxic drug such as docetaxel.…”
Section: Iron–gold Bifunctional Nanoparticlesmentioning
confidence: 99%
“…Importantly for the practical realization of the DTX@HNT/Au-SORT synergy, low temperatures of the disruption of the HNT hydrogen bonding in DTX@HNT/Au-SORT at low pH can be conveniently reached through the PPTT-heating of the AuNPs [ 6 ]. This enables facile implementation of the DTX@HNT/Au-SORT design based on the synergy of the PPTT and targeted release of DTX incorporated in HNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional cancer therapy relies upon the administration of cytotoxic chemical agents resulting in multiple negative side effects of chemotherapy due to the susceptibility of normal cells to this treatment [ 1 , 2 ]. Current strategies to minimize these side effects involve different approaches for targeted drug delivery to specific tissues [ 3 5 ], including magnetically driven transport of therapeutic agents [ 6 8 ], and/or incorporation of the specific biomolecules, such as aptamers [ 9 ], peptide sequences [ 10 ], and antibodies [ 11 ] onto the surface of the nanoscale carriers for selective delivery of the anti-cancer medication [ 12 , 13 ]. There are two main types of cancer cells to target: (1) cancer stem cells (CSCs) that could develop into different cell types [ 14 ], and (2) differentiated cancer cells (DCCs) that have matured into a particular form of cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, nanotechnology has attracted much attention in various elds. 1,2 One of the most inuential families of nanomaterials is magnetic nanoparticles, which have been extensively employed in different sciences, including drug delivery, 3 illness recognition, 4 water desalination, 5 ambiance scrubbing, 6 and chemical catalysis. 7 Recently, magnetic nanocatalysts have attracted the consideration of many researchers due to their high activity, selectivity, availability, large surface area, low toxicity, excellent reusability, and easy separation.…”
Section: Introductionmentioning
confidence: 99%